Argentina and South Africa facing the challenges of the XXI Century : Brazil as the mirror image - Lechini, Gladys (2011)
In my early approaches to the study of Argentina’s relations with the African countries, there always appeared an African policy developed by Brazil as comparative reference. The implementation of that policy since the independence obtained by the African countries, with successful designs and strategies, offered a contrast with Argentina’s so-called “lost opportunities” in Africa.